Projection of population of stunted children under five years and anaemic women of reproductive age in thirteen low, upper and high income 100 million+ countries around the world up to 2050 - Raut, Manoj Kumar; Sahu, Ananta Basudev (International Journal Of Community Medicine And Public Health, 2018)
Background: In 2012, the World Health Assembly Resolution 65.6 endorsed a comprehensive implementation plan on maternal, infant and young child nutrition, which specified a set of six global nutrition targets that by 2025. The goals were aimed at reducing stunting, anaemia, low birth weight, no increase in childhood overweight, increase rates of exclusive breastfeeding and reduce and maintain wasting. Out of these an average annual rate of reduction (AARR) of 3.9% for a 40% reduction in reduction in the number of children under five years of age who are stunted and an average annual rate of reduction of 5.2% has been estimated for a 50% reduction in anaemia among women of reproductive age. Methods: This paper uses demographic techniques to project the number of stunted children under five years and anaemic women for the thirteen 100 million plus countries as of UN population projections, 2017 of Philippines, Ethiopia, Japan, Mexico, Russian Federation, Bangladesh, Nigeria, Pakistan, Brazil, Indonesia, United States of America, India and China using average annual rate of reduction recommended in the world health assembly. Results: The number of stunted children under five years of age is estimated to be reduced by 27% by 2025, 40% by 2030 and 72% by 2050. The number of anaemic women of reproductive age is estimated to be reduced by 32% by 2025, 46% by 2030 and 85% by 2050. Conclusions: There is a dire need for accelerating the progress of reduction in stunting prevalence among children under five years and anaemia among women of reproductive age to achieve the global targets in selected high burden countries of India and Nigeria.